Machining performance of vegetable oil with phosphonium- and ammonium-based ionic liquids via MQL technique - Amiril Sahab, Abdul Sani; Erween, Abd Rahim; Safian, Sharif; Hiroyuki, Sasahara (Elsevier, 2019)
Thermo-mechanical loads are the main factor that influences the tool wear and product surfaces during machining processes. Lubrication in metal cutting is an effective medium to reduce frictional forces and wear on the tool-workpiece interfaces. On this regards, the advantages of using refined bio-based metalworking fluids (MWFs) with the presence of low toxic, biocompatible and oil-miscible ionic liquids (ILs) additives ([N1,8,8,8][NTf2] (AIL) & [P6,6,6,14][(iC8)2PO2] (PIL)) at nominal weight concentrations of 1, 5 and 10% are explored during orthogonal cutting of AISI 1045 steel. Accordingly, the lubricants are supplied via minimum quantity lubrication (MQL) technique and comparative studies are conducted against the performance of the neat modified Jatropha-based lubricant (MJO) and commercially available synthetic ester-based MQL cutting fluid (SE). The combination of mist supply of the MJOs during machining have a great impact on cleaner production that eliminates the excessive usage of fluids and supports the utilization of environmentally friendly chemicals. This work extends the application of a minute quantity of fully miscible ILs in polar vegetable-based MWF which proven to provide a significant improvement on the lubrication effect of the MJO. MJOþAIL10% and MJOþPIL1% showed the best cutting performance amongst all lubricant mixtures with reduction of cutting forces and specific cutting energy by 4 to 5%, cutting temperatures by 7 to 10%, friction coefficient by 2 to 3%, tool-chip contact length by 8 to 11%, chip thickness by 22 to 25%, friction angle by 1 to 2% and increased shear angle by 25 to 29% compared to the SE. Besides, the effect of low friction and reduced cutting forces produced lower specific cutting energy that promotes “greener” and more sustainable working environment.